2020
DOI: 10.1039/d0fo00427h
|View full text |Cite
|
Sign up to set email alerts
|

Superior hypoglycemic activity of mulberry lacking monosaccharides is accompanied by better activation of the PI3K/Akt and AMPK signaling pathways

Abstract: Mulberry removed monosaccharides (FM) displayed better hypoglycemic activity than untreated mulberry (MP), which may be attributed the stronger effects of FM on activating PI3K/Akt and AMPK signaling pathways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 35 publications
2
9
0
Order By: Relevance
“…Li et al studied the sugar‐reducing rate of different microorganisms of mulberry, and the result verified that the degradation rate of fructose and glucose was 86.49% and 66.12% respectively after fermentation by lactobacillus (Li et al., 2017). In our previous study (Long et al., 2020), we have confirmed that the fermented mulberry plays the better hypoglycemic effect than the unfermented mulberry in T2DM mice, which may be related to the change of bioactive substance content. After mulberry fermentation, the content of anthocyanins decreased, the content of 1‐deoxyricogen increased significantly, and the content of polyphenols and flavonoids remained unchanged.…”
Section: Introductionsupporting
confidence: 60%
See 2 more Smart Citations
“…Li et al studied the sugar‐reducing rate of different microorganisms of mulberry, and the result verified that the degradation rate of fructose and glucose was 86.49% and 66.12% respectively after fermentation by lactobacillus (Li et al., 2017). In our previous study (Long et al., 2020), we have confirmed that the fermented mulberry plays the better hypoglycemic effect than the unfermented mulberry in T2DM mice, which may be related to the change of bioactive substance content. After mulberry fermentation, the content of anthocyanins decreased, the content of 1‐deoxyricogen increased significantly, and the content of polyphenols and flavonoids remained unchanged.…”
Section: Introductionsupporting
confidence: 60%
“…In our previous study (Long et al, 2020), we have confirmed that the fermented mulberry plays the better hypoglycemic effect than the unfermented mulberry in T2DM mice, which may be related to the change of bioactive substance content. After mulberry fermentation, the content of anthocyanins decreased, the content of 1-deoxyricogen increased significantly, and the content of polyphenols and flavonoids remained unchanged.…”
Section: Introductionsupporting
confidence: 53%
See 1 more Smart Citation
“…FAK may activate the PI3K/Akt signaling pathway and induce cellular mobility, migration and invasion [ 36 ]. Previous studies have confirmed that PI3K may induce the phosphorylation of the serine residues 308 and 473 of Akt [ 37 , 38 ]. Phosphorylated Akt (p-Akt) can phosphorylate GSK3β and inhibit its kinase activity, leading to the inactivation of GSK3β [ 39 ].…”
Section: Discussionmentioning
confidence: 86%
“…It has been reported that there is decreased HK and PK activity in diabetic animals. 58,65 Herein, the contents of hepatic HK and PK were decreased in the diabetic mice, while they were increased slightly in the mice treated with the EN formulas. This result confirmed that the EN formulas could directly or indirectly affect hepatic enzyme activity, and soy protein had a greater impact than whey protein.…”
Section: Discussionmentioning
confidence: 91%